2011
DOI: 10.1126/science.1202977
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-Enhanced Transport in Photonic Quasicrystals

Abstract: Quasicrystals are aperiodic structures with rotational symmetries forbidden to conventional periodic crystals; examples of quasicrystals can be found in aluminum alloys, polymers, and even ancient Islamic art. Here, we present direct experimental observation of disorder-enhanced wave transport in quasicrystals, which contrasts directly with the characteristic suppression of transport by disorder. Our experiments are carried out in photonic quasicrystals, where we find that increasing disorder leads to enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
129
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(131 citation statements)
references
References 29 publications
1
129
0
1
Order By: Relevance
“…The beam width increases slowly indicating stronger confinement, and the slope of the curve smoothly changes. The calculated exponents for 30 • , 45 • and 90 • are close to 0.5, indicating that wave propagation in the quasicrystal is diffusive-like 3,26 .…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…The beam width increases slowly indicating stronger confinement, and the slope of the curve smoothly changes. The calculated exponents for 30 • , 45 • and 90 • are close to 0.5, indicating that wave propagation in the quasicrystal is diffusive-like 3,26 .…”
mentioning
confidence: 69%
“…However, the bandgap is very narrow and loosely defined thus exhibiting characteristics of pseudogaps 16 . Indeed, a previous study 3 demonstrated that a quasicrystal has pseudogaps. Since localized states can exist in the pseudogap regime 16 , the wave localization is expected to occur in the low-intensity spectral regime of the quasicrystal.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The method of parabolic equation approximation was first applied by Leontovich in study of radio-waves spreading [16] and later developed in detail by Khokhlov [17] (see also [18]). In modern experimental and theoretical research, it naturally appears in investigations of a wave propagation in random optical lattices [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In optics, for instance, photonic quasicrystals have attracted strong interest [3] for their specific behaviour, induced by the particular spectral properties, in light transport [4][5][6], plasmonic [7] and laser action [8]. Very recently, one of the most salient spectral feature of quasicrystals, namely the gap labelling [9], has been observed for a polariton gas confined in a one dimensional quasi-periodic cavity [10].…”
mentioning
confidence: 99%